Protein Kinase G Is Involved in Acute but Not in Long-Term Regulation of Renin Secretion - Schramm, Andrea; Schweda, Frank; Sequeira-Lopez, Maria Luisa S.; Hofmann, Franz; Sandner, Peter; Schlossmann, Jens (Frontiers in Pharmacology, 2019)
Pharmacological inhibition of the renin-angiotensin-aldosterone-system (RAAS) is, in combination with diuretics, the first-choice treatment for hypertension, although 10-20% of patients do not respond adequately. Next to the RAAS, the nitric oxide/cGMP/protein kinase G (PKG) system is the second fundamental blood pressure regulator. Whether both systems influence each other is not well studied. It has been shown that nitric oxide (NO) supports renin recruitment via activation of soluble guanylate cyclase (sGC) and subsequent generation of cGMP. Whether this leads to an ensuing activation of PKGs in this context is not known. PKGIα, as well as PKGII, are expressed in renin-producing cells. Hence, we analyzed whether these enzymes play a role regarding renin synthesis, secretion or recruitment. We generated renin-cell specific PKGI-knockout mice and either stimulated or inhibited the renin system in these mice by salt diets. To exclude the possibility that one kinase isoform can compensate the lack of the other, we also studied double-knockout animals with a conditional knockout of PKGI in juxtaglomerular cells (JG cells) and a ubiquitous knockout of PKGII. We analysed blood pressure, renin-mRNA and renal renin protein content as well as plasma renin concentration. Furthermore, we stimulated the cGMP-system in these mice using BAY 41-8543, a sGC-stimulator and examined renin regulation either after acute administration or after 7 days (application once daily). We did not reveal any striking differences regarding long-term renin regulation in the studied mouse models. Yet, when we studied the acute effect of BAY 41-8543 on renin secretion in isolated perfused kidneys as well as in living animals, we found that administration of the substance led to a significant increase in plasma renin concentration in control animals. This effect was completely abolished in double knockout animals. However, after 7 days of once daily application, we did not detect a persistent increase in renin mRNA or protein in any studied genotype. Therefore, we conclude that in mice cGMP and PKG are involved in the acute regulation of renin release but have no influence on long-term renin adjustment.